KEDUDUKAN LEGALITAS SURAT PERNYATAAN PELEPASAN HAK MILIK ATAS TANAH YANG DIBUAT OLEH LURAH (Studi Kasus ATR/BPN Depok Jawa Barat) - Nurul Hidayati (Program Magister Ilmu Hukum Universitas Pancasila, 2022)
The document is one of the important things that must be owned by someone who has rights over his property, in this case what is meant by land. If someone owns land, there must be an official written document to prove that the land is his property. Then if the owner wants to sell then there needs to be a change of status and several conditions to relinquish his land rights, one of which is the SPPHT (Surat Pernyataan Pelepasan Hak Tanah). In the SPPHT issue, the Depok area, namely that there were village heads who wanted to control the management of the Declaration of Relinquishment of Land Rights, where in terms of management, each land law official had their respective roles. From the description above it is clear that the lurah’s position is within the scope of the witness, but in practice there are still unscrupulous lurahs who interfere in the management of the SPPHT. Therefore the writing of this thesis raises the title “STATUS AND LEGALITY OF THE STATEMENT OF RELEASE OF LAND PROPERTY RIGHTS MADE BY THE LURAH”author found a problem in one of the ATR/BPN land administration areas in the